2012 16th International Symposium on Electromagnetic Launch Technology 2012
DOI: 10.1109/eml.2012.6325161
|View full text |Cite
|
Sign up to set email alerts
|

Actively controlling the muzzle velocity of a railgun

Abstract: The muzzle velocity variation is a parameter of many kinds of accelerators. Actively reducing this value is achieved by observing the motion of the accelerated object during launch and by adjusting the propelling force to achieve the desired velocity. Applying this method to classical gas guns requires a controllable energy source. Experiments with Busy Lizzie type gas-driven accelerators resulted in limited success due to severe energy transfer and timing problems. The railgun overcomes these limitations as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…At the ISL, we have recently pursued two projects in the field of materials science. The first project was related to the realization of a symmetric Taylor test [2]. It can be shown that railguns are very well suited to control the exit velocity and exit time by implementing a feedback circuit.…”
Section: Introductionmentioning
confidence: 99%
“…At the ISL, we have recently pursued two projects in the field of materials science. The first project was related to the realization of a symmetric Taylor test [2]. It can be shown that railguns are very well suited to control the exit velocity and exit time by implementing a feedback circuit.…”
Section: Introductionmentioning
confidence: 99%